1998
DOI: 10.1152/jappl.1998.85.4.1471
|View full text |Cite
|
Sign up to set email alerts
|

Leg mass and lower body negative pressure tolerance in men and women

Abstract: To explore the hypothesis that lower body muscle mass correlates with orthostatic tolerance, 18 healthy volunteers (age 18-48 yr; 10 men, 8 women) underwent a graded lower body negative pressure (LBNP) protocol consisting of six, 5-min stages of suction up to 60 mmHg in 10-mmHg increments. Forearm blood flow, heart rate, and blood pressure were measured, and forearm vascular resistance was calculated. Leg muscle mass was assessed by dual-energy X-ray absorptiometry. All subjects received standard intravenous h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…Another factor that might make the women in the present study more susceptible is their smaller body size and muscle mass (19,30,37). The influence of muscle mass on orthostatic tolerance is controversial: one report indicated that greater muscle mass may be associated with greater orthostatic tolerance (25), whereas another did not (23). Difference in size is probably not the primary reason for the intergroup differences in the present study for two reasons.…”
Section: Discussionmentioning
confidence: 74%
“…Another factor that might make the women in the present study more susceptible is their smaller body size and muscle mass (19,30,37). The influence of muscle mass on orthostatic tolerance is controversial: one report indicated that greater muscle mass may be associated with greater orthostatic tolerance (25), whereas another did not (23). Difference in size is probably not the primary reason for the intergroup differences in the present study for two reasons.…”
Section: Discussionmentioning
confidence: 74%
“…On the other hand, calf skeletal muscle hypertrophy from chronic resistance exercise training has been reported to reduce leg compliance (23,32). Lawler et al (22) tested the hypothesis that subjects with less leg muscle (dual energy X-ray absorptiometry) would have increased venous blood pooling during lower body negative pressure (LBNP) and an increased propensity toward orthostatic intolerance (22). These authors reported no association between lower extremity lean tissue and orthostatic tolerance and concluded that alterations in muscle mass that were not associated with specific interventions, such as bed rest or resistance training, did not predict a response to LBNP (22).…”
Section: Discussionmentioning
confidence: 99%
“…Lawler et al (22) tested the hypothesis that subjects with less leg muscle (dual energy X-ray absorptiometry) would have increased venous blood pooling during lower body negative pressure (LBNP) and an increased propensity toward orthostatic intolerance (22). These authors reported no association between lower extremity lean tissue and orthostatic tolerance and concluded that alterations in muscle mass that were not associated with specific interventions, such as bed rest or resistance training, did not predict a response to LBNP (22). The specific effect of chronic spinal cord injury on the relationship among lower extremity muscle, leg compliance, and orthostatic tolerance has not been thoroughly investigated, and the report herein is a preliminary view of these complex associations.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, the subjects were very well-trained divers and a great increase in compliance of 108% after bed rest was reported. In prior studies, increased compliance has been shown to be correlated to reduction in calf muscle volume (10,12), and muscle atrophy has been postulated as an explanation for increased compliance, resulting in orthostatic intolerance in some (5, 6, 10-12, 33), but not all (27), studies. However, in the present study no leg or arm volume changes were observed during the bed rest period, indicating only minor muscle atrophy.…”
Section: Comparison With Previous Bed Rest and Spaceflight Studiesmentioning
confidence: 98%